2021
DOI: 10.1111/hsc.13554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on community services for homebound older adults in New York City

Abstract: The ongoing COVID-19 global pandemic has had a significant impact on the physical health, psychological well-being and daily routine of older adults. In the United States, 80% of Americans who died from COVID-19 were older adults (aged 65 or older; Centers for Disease Control & Prevention, 2021a). Although the group aged 18-49 accounted for 49% of infections, more older adults were hospitalised (47%) than the age groups of 50-64 (26%) and 18-49 (24%; Centers for Disease Control & Prevention, 2021b). Older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Despite their unique strengths, community-level organisations and initiatives encountered various challenges during the COVID-19 pandemic. As documented elsewhere, COVID-19-related challenges faced by community-based organisations included restrictions on movement, closure of physical spaces, reduced capacity for in-person services, and limited face-to-face interactions due to social distancing measures (27)(28)(29). Considering the importance of physical accessibility and provision of tailored personal guidance, many organisations tried their best to stay operational.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their unique strengths, community-level organisations and initiatives encountered various challenges during the COVID-19 pandemic. As documented elsewhere, COVID-19-related challenges faced by community-based organisations included restrictions on movement, closure of physical spaces, reduced capacity for in-person services, and limited face-to-face interactions due to social distancing measures (27)(28)(29). Considering the importance of physical accessibility and provision of tailored personal guidance, many organisations tried their best to stay operational.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, older adults are anecdotally less accustomed to and involved in the online world of social media and communications. Older adults have experienced difficulties with telecommunications; telephone interaction has not been favourable given the hearing impairment of some older and challenges in engaging individuals and building rapport [43]. Online technologies and resources could be harnessed to provide social support networks and promote future inclusivity for older adults [44].…”
Section: Older People and Covid-19mentioning
confidence: 99%
“…For example, COVID-19 has been linked to an increase in symptoms of depression among undergraduate students. Santander-Hernández et al [13] reported that depressive symptoms were present in 78% of their participants, a much higher estimate than 27% which was found in a meta-analysis before the pandemic [14]. Moreover, analysis of data from the English Longitudinal Study of Ageing (ELSA), which includes adults aged 52 and over, found that the prevalence of clinically signifcant depressive symptoms increased from 12.5% prepandemic to 28.5% in November 2020 [15].…”
Section: Introductionmentioning
confidence: 99%